Community Empowerment By Shredded Catfish Production As An Effort To Revilitize Health Service Post At Gading Kulon District, Malang Regency - Lilik Supriati (Journal of Innovation and Applied Technology, 2015)
ABSTRACT The aim of this community service is to optimalize the integrated health service post in increasing toddler development. We held some health education and training to its cadet about integrated health service post management and repair some Posts facilities. Other purpose is to develop entrepreneurship among Flamboyan cadet post collaborating with catfish farmer in Gading Kulon Malang Regency. The catfish was processed as dried shredded catfish that hygienic, nutritious, and high selling values. The result of these activities was accomplishment of 100% of cadets’ knowledge and skill in post management. During the development screening, there were 25norm toddler participants.The corporation with catfish farmer produced a pilot catfish pond and independent funds from dried shredded catfish selling. Survey result to 20 consumers shows that 90% of them were satisfied to the taste of dried shredded catfish. Keyword: community empowerment,dried shredded catfish, independent integrated health service post revitalization